Particle Size Dependence of TiO2 Electrodes in Rechargeable Lithium Battery - S. Y. Huang; G. Campet; N. Treuil; J. Porter; K. Chhor (Active and Passive Electronic Components)
Particle size effects in five anatase TiO2 pellet electrodes with different particle sizes (4 ∼ 300nm) and surface areas (8 ∼ 380m2/g) were studied by XRD analysis, chronopotentiometry and chronoamperometry in Li/LiN(CF3SO2)2 + EC:DME/TiO2 cells. Nanosized TiO2 electrodes showed by 22% larger storage capacity, 50% lower overvoltage loss at the same current density, and 75% higher charge density for a given time than microsized ones; electric storage capacity enhances more rapidly with decreasing particle size and increasing surface area in a nanoscale region than in a microscale region. The particle size dependence may be explained by surface morphology of electrodes and existence of structural defects or distortion in the surface layer of TiO2 nanosized particles.